2020
DOI: 10.1186/s12913-020-05106-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of digital nursing technologies: development of a comprehensive digital nursing technology outcome framework based on a scoping review

Abstract: Background: Digital nursing technologies (DNT) comprise an expanding, highly diverse field of research, explored using a wide variety of methods and tools. Study results are therefore difficult to compare, which raises the question how effectiveness of DNT can be adequately measured. Methods currently used might not be sufficient for certain specific nursing contexts. A comprehensive outcome framework that shows the multitude of possible outcome areas could be useful to generate more comparable results. The ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 77 publications
0
22
0
1
Order By: Relevance
“…The goal was to identify frameworks of relevance to the nursing context according to the inclusion and exclusion criteria described further below. The search components comprised: (i) a systematized literature search conducted in PubMed; (ii) a narrative review was carried out by searching google scholar, screening already identified literature [ 4 ] and reference lists of the systematically identified articles; (iii) information on relevant frameworks collected from four experts in the field of evaluation from the German “Cluster Zukunft der Pflege” (Future of Care Cluster) [ 13 ]. In this joint project, regular evaluations of digital nursing technologies have been and are carried out over the period 2017–2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal was to identify frameworks of relevance to the nursing context according to the inclusion and exclusion criteria described further below. The search components comprised: (i) a systematized literature search conducted in PubMed; (ii) a narrative review was carried out by searching google scholar, screening already identified literature [ 4 ] and reference lists of the systematically identified articles; (iii) information on relevant frameworks collected from four experts in the field of evaluation from the German “Cluster Zukunft der Pflege” (Future of Care Cluster) [ 13 ]. In this joint project, regular evaluations of digital nursing technologies have been and are carried out over the period 2017–2022.…”
Section: Methodsmentioning
confidence: 99%
“…This article refers to digital nursing technology (DNT) as defined by Krick et al 2019 [ 2 ] and Krick et al 2020 [ 4 ]. DNT are technologies that fulfil one or all of the following criteria: i) “support the immediate action of a caregiver”; or ii) “contribute to the self-reliance of the person in need of care in such a way that direct on-site care assistance can be avoided”; or iii) “substitute the nursing support by using technology”, or iv) “support the training or education of nurses” [ 4 ]. The focal points of this article are the aspects i-iii.…”
Section: Introductionmentioning
confidence: 99%
“…Semuanya ini membantu perawat dalam memperoleh informasi tentang pasien yang dirawatnya dan membantu mereka dalam memberikan perawatan yang tepat. Digital Nursing Technology (DNT) diperlukan untuk membantu tindakan keperawtan yang cepat (seperti dalam guidline pengambilan keputusan), mengurangi kehadiranlangsung perawatan, menghadirkan pengganti perawat seperti robot (Krick et al, 2020). Sebaliknya hasil penelitian menunjukan responden menyatakan diri masih "pemula" dalam hal: Saya mengetahui bahwa teknologi termasuk pengelolaan alat tenun (mean 2.18); Saya mampu menggunakan wireless sebagai sarana komunikasi dengan tim medis yang lain (mean 2.33); dan Saya mampu mengobservasi pasien yang menggunakan tracheostomy, stoma, dll (mean 2.49).…”
Section: Metodeunclassified
“…The possible effects that these technologies aim at cover a wide-ranging field. [7][8][9] The quality of life (QoL) of people in need of care may be improved, [10][11][12] and the independence of people potentially in need of care may be supported by technology such that they are able to continue living independently at home with minimum or no nursing support. [13][14][15][16] Psychological or physical support for formal caregivers can have a beneficial effect on their health 17,18 and thus might, for instance, enable older employees to work longer; support for informal caregivers may relieve them to the extent that they can cope without additional formal care support.…”
mentioning
confidence: 99%